Conflict over natural resources in South-East Asia and the Pacific - Teck Ghee, Lim, ed (Manila : ADMU Press, 1990)
c.2
Keywords: Natural resources -- Asia, Southeastern; Natural resources -- Asia; Natural resources -- Pacific area